EFEKTIVITAS MICROCIDE 100/100 EC TERHADAP SERANGAN JAMUR BIRU PADA KAYU KARET (Hevea brasiliensis Muell.Arg.) (Effectiveness of Microcide 100/100 EC to Restrain Blue Mushroom Attack on the Rubber Wood (Hevea brasiliensis Muell.Arg.): Gimson Luhan, M. Damiri, John F. Gustaf dan Marthinus Lambung - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACT The objectives of this research are to know the value of adsorption and the influence of microcide using dyeing method against the intensity of blue mushroom attack on the rubber wood (Hevea brasiliensis Muell.Arg.) in the axial direction, the base (P), the middle (T) and the end (U). The expected benefit is to be an input in finding alternative use of preservative composition that is able to suppress the growth rate of blue mushroom so as to improve the quality of rubber wood usage. The results showed that the value of microcide preservative adsorption on wood has a tendency of increasing value with increasing concentration of microcide preservative and largest in the concentration of 1% Microcide preservative by 2.11 g/cm2. The calculation result of the intensity of blue mushroom attack on rubber wood at Microcide concentration of 1% is 5,53% including the classification is not meaningful, so it is effective to prevent blue fungus attack. The result of the measurement of the decrease of the rubber wood water content per week has a tendency of decreasing value from week I to week V. The decrease of the water content of timber that occurs almost uniformly for each level of Microcide concentration per week, so that in week V the water content of wood ranges from 18% - 19, 73%. The fresh water content of rubber wood used in this research ranged 61.34% - 84.67%, with the condition of the water content allows the fungal attack on rubber wood. The intensity of blue mushroom attack between week I - IV at moisture content between 69,16% - 27,50% shows optimum blue fungus growth, while under condition of fiber saturation point entering week V (18,86%) mushroom growth value is very small. Further research on the preservation of rubber wood by dipping method using Microcide EC preservative on wood resistance to other types of fungi. Keywords: Adsorption value, attack intensity, microcide, rubber wood.